Context and Catholicity in the Science and Religion Debate Intercultural contributions from French-speaking Africa - Bom, Klaas (Theology and Mission in World Christianity, 2020)
Based on a thorough study of the 'lived theology' of Christian students and university professors in Abidjan, Kinshasa and Yaoundé, this book proposes a theoretical framework that makes an intercultural and interdisciplinary debate on science and religion possible. ; Readership: All interested in the current debate on science and religion and its cultural and historical background and anyone interested in African Christianity, African Modernities and Intercultural Theology.